2000
DOI: 10.1161/01.str.31.12.2925
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias and Stroke

Abstract: Background and Purpose-With the exception of atrial fibrillation (AF), little scientific attention has been given the associations between cardiac arrhythmias and incidence of stroke. We sought to study whether atrial and ventricular arrhythmias assessed during a 24-hour ambulatory ECG registration are associated with incidence of stroke. Methods-The population-based cohort "Men Born in 1914" was examined with 24-hour ambulatory ECG registrations at 68 years of age. Four hundred two men without previous myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…We also showed that stroke of undetermined etiology and cardioembolic stroke with a prior history of PAF were similarly associated with frequent PAC. These results of the present study confirm the findings of previous studies showing an association between frequent PAC and stroke [8, 9]. Further prospective studies are needed to clarify the risk of stroke in patients with frequent PAC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also showed that stroke of undetermined etiology and cardioembolic stroke with a prior history of PAF were similarly associated with frequent PAC. These results of the present study confirm the findings of previous studies showing an association between frequent PAC and stroke [8, 9]. Further prospective studies are needed to clarify the risk of stroke in patients with frequent PAC.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesized that a certain population with stroke of unknown etiology should have latent PAF and such patients should be associated with frequent PAC. Engstrom et al [8] reported that the risk of ischemic and hemorrhagic stroke in men is associated with a high frequency of atrial ectopic beats. Wallmannn et al [9] reported that a high frequency of atrial premature beats in ischemic stroke patients predicts PAF.…”
Section: Introductionmentioning
confidence: 99%
“…An association between frequent PAC on 24-hour ECG recordings and an increased incidence of PAF in patients with ischemic stroke was also demonstrated [25]. A large array of evidence demonstrates that AF is triggered by multifocal abnormal electrical activity that usually originates in the pulmonary veins [26]. Thus, PAC is one trigger of AF.…”
Section: Discussionmentioning
confidence: 99%
“…The Nexstim system's 6-channel EMG module (SR = 1450 Hz, cut-off frequency of 350 Hz for the low pass filter) automatically calculated the motor evoked potential (MEP) amplitudes and latencies as the motor cortex (cortex area of the thumb) is stimulated [34]. Disposable Ag-AgCL surface electrodes were used to record the MEP responses that were displayed in a computer screen in order to assess the validity of the response based on the strength of MEPs reflecting the ability of that area to develop muscle contraction.…”
Section: Methodsmentioning
confidence: 99%
“…During seizures, bradycardia and asystole states can occur in some patients. Stroke can also alter the heart rhythm [34] and intense emotions can disrupt significantly the heart rate and blood pressure of a given patient [35]. An illustration of the PQRST deflections of the heart is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%